Major depressive disorder and generalized anxiety disorder show different autonomic dysregulations revealed by heart‐rate variability analysis in first‐onset drug‐naïve patients without comorbidity. Issue 2 (February 2017) - Shinba, Toshikazu
Abstract : Aim: The aim of the present study was to examine whether depression and anxiety disorder manifest different autonomic dysregulations using heart‐rate variability (HRV) and heart rate (HR) measurements. Methods: HRV and HR were recorded both at rest and during task execution (random‐number generation) in first‐onset drug‐naïve patients with major depressive disorder (MDD, n = 14) and generalized anxiety disorder (GAD, n = 11) as well as in healthy controls ( n = 41). The patients showed no comorbidity of depression and anxiety disorder. GAD patients did not exhibit panic or phobic symptoms at the time of measurement. Following power spectrum analysis of HR trend, the high‐ (HF) and low‐frequency (LF) components, the sum (LF + HF), and the LF/HF ratio were compared among the groups. Results: In the MDD patients, as previously reported, HF was low and the LF/HF ratio was high during the initial‐rest condition, and HF was less reactive to the task. In contrast, GAD patients showed significantly high HF, although autonomic reactivity was not impaired. Conclusion: The results indicate that baseline autonomic activity and its reactivity to behavioral changes are different between MDD and GAD in the early stage of illness. High parasympathetic tone in GAD may reflect responses of the parasympathetic system to anxiety. MDD is accompanied by an autonomic shift toward sympathetic activation and a reduced reactivity to task.